Effect of applied magnetic field on ZnFe alloy electrodeposition - Issaadi, H. Kermoune; Baouz, T.; Levesque, A.; Douglad, J.; Rehamnia, R.; Chopart, J. P. (Journal of the Indian Chemical Society, 2024)
Corrosion-resistant materials for the protection of structures are of paramount importance to the industry. This research work reports on the effects of a magnetic field applied parallel to a working electrode on the electrodeposition process of the corrosion-resistant ZnFe alloy coating. The electrochemical study of ZnFe alloy coatings prepared using an acid sulfate bath was carried out in galvanostatic mode. The results indicated that the current density and magnetic field have remarkable effects on the formation kinetics of the ZnFe deposits. The diffusion rate of the Fe ferromagnetic species subjected to mass transport accelerated under the influence of the Lorentz force (applied magnetic field); moreover, these ions were deposited in large amounts under the effect of the magnetic field. The energy-dispersive X-ray (EDX) spectroscopy analysis confirmed the modification of the Fe ion atomic concentrations in the ZnFe coatings under the influence of the magneto-hydrodynamic (MHD) convection compared to those deposited without the imposition of the magnetic field. The morphological examinations revealed that the magnetic field acted positively on the deposited layers by endowing them with homogeneous surfaces. The X-ray diffraction (XRD) analysis of ZnFe deposits demonstrated the presence of delta (δ), zeta (ξ) and eta (η) phases when there was no applied magnetic field. Furthermore, depending on the magnitude of the applied magnetic field, XRD diagrams exhibited changes in crystallographic orientation, grain size, and the electro-crystallization. These changes favor the presence of certain crystallographic phases, such as (200) and (330).
Keywords: Codeposition; Magnetic field; Structure; ZnFe alloy